The application of competition law in the airline industry in Malaysia - Hamdan, Norahimah Fitri Binti Mohd (2019)
As the world economy is moving towards full liberalisation, competition law plays an important role in the regulation of anti-competitive practices and the need to have appropriate competition law and policy in developing countries is becoming crucial. There are issues and challenges faced by these countries but international best practices and experiences from advanced and matured jurisdictions are an important influence and provide a useful guidance. The thesis aims to explore and investigate the application of completion law in the Malaysian airline industry through the insights drawn from the application of the competition laws in the EU airline industry based on its established laws and jurisprudence. From the institutional perspective, Malaysia faces great challenges in providing competition expertise in its enforcement agencies and judiciary. This investigation is timely and important. Competition legislation has only been in place in Malaysia since 2010 and sector specific regulation, including competition regulation, was only enacted for the airline industry in 2015. The establishment of two separate independent bodies by this legislation (MyCC and MAVCOM) may have the potential to create uncertainties and inconsistencies in implementing the law in the industry. Legal certainty is particularly important for the treatment of anti-competitive agreements for a developing jurisdiction like Malaysia. Malaysian competition legislation is largely based on EU competition law and this together with the international nature of the airline industry makes the EU jurisprudence highly authoritative. It is to be cautioned however, any reference to the EU jurisprudence must take into account the different economic structure of a developing country where there is a general lack of competition culture and awareness.